Stakeholders’ Perception On Civic-Education Practices Of Upper Basic Students In Kwara, Nigeria - AUN, Thompson Toryuha; Modupe , Olakunle; Hassan , Aliyu Kehinde; Yusuf , Salawu; Muideen Omotola, Omoloso, (Equilibrium: Jurnal Pendidikan, 2026)
The study investigated stakeholders’ perception on civic-education practices of upper-basic students in Kwara, Nigeria. The design for the study was a descriptive survey, A total of 391 participants were selected using simple random sampling, comprising 107 teachers, 256 students, and 28 parents and community leaders, ensuring a representative sample across public and private schools and a diversity of educational qualifications and experiences. The study employed multistage sampling techniques. Data were collected using a researcher-designed questionnaire, Stakeholders’ Perception of Civic Education Practices in Upper Basic Schools Questionnaire (SPCEPSQ), consisting of two sections: demographic information and 15 items assessing perceptions of civic education and its impact on student engagement. Findings of the study revealed among others that; majority of teachers in Kwara agree that Civic Education enhances student engagement, highlighting its perceived value in fostering civic responsibility and participation; parents believed that the subject promotes responsibility and active participation, administrators affirm that it fosters discipline and social awareness. The study concludes that, there is urgent need for multi-level reforms aimed at strengthening the implementation of Civic Education such as specialized teacher training, adoption of learner-centered pedagogies, curriculum modernization, and stronger policy frameworks backed by sufficient resources and political will